The assessment of financial literacy: New evidence from Europe - Gianni Nicolini; Marlene Haupt (International Journal of Financial Studies, 2019)
The hypothesis that people with more financial literacy make better financial decisions and show positive financial behaviors is crucial for more than one stakeholder. A weak connection between financial literacy and financial behaviors jeopardizes the opportunity to invest in financial education and to develop a consumer protection framework based on the chance to develop aware and responsible financial consumers. This study uses data from different countries (Germany, France, Italy, Sweden, the UK), using surveys devised and fielded specifically to measure financial literacy and in order to assess if the availability of a broad set of items on financial literacy allows to develop new measures of financial literacy to better understand the relationship between financial literacy and financial behaviors. The well-established Lusardi–Mitchell questions are compared with measures that differ in terms of number of items (the "50-items"), range of topics (the "5-specific" index), or selection process of the items (the "unbiased" index). Results support the hypothesis that the Lusardi-Mitchell questions remain a good measure in a first-step analysis, but a deeper understanding of the connection between financial literacy and financial behaviors benefits from the measures proposed in the study, that should be considered as additional assessment tools in financial literacy research.
Keywords: G5; G53; 330; consumer finance; financial education; financial literacy